The Epidemiologic and Sociodemographic Features of Superficial Fungal Infection Among Children in East Java Suburban Public Hospital - Prakoeswa, Flora Ramona Sigit; Pramuningtyas, Ratih; Dimawan, Rully Setia Agus (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Superficial fungal infection is a common skin disease among children, causing morbidity and reducing quality of life. The disease's prevalence and etiological agents change with geographic area, age, humidity, and sex. The data on this matter is still limited in Indonesia. Purpose:  To determine the current epidemiologic and sociodemographic features of superficial fungal infection among children. Methods: This descriptive study examined all the pediatric inpatients and outpatients at the Department of Dermatology and Venerology of East Java suburban Public Hospital in Indonesia from 2016 to 2020 who met the inclusion criteria. Result:  From 2016 to 2020, the number of fungal infection patients was 12.3% (n = 175) among 1,427 dermatology patients. Pityriasis versicolor (PVC) is the most common fungal skin disease (4.1%), followed by tinea capitis (2.2%), tinea cruris (1.6%), and tinea corporis (1.4%). Subjects aged 6 to 12 years old were the most likely to be infected with a fungus. Boys were more likely to develop this infection. Conclusion: From 2017 to 2020, there was a downward trend in children's superficial fungal infections. Pityriasis versicolor (PVC) is a fungal skin ailment that cause the most cases compared to other fungal infections. Boys and children between the ages of 6 to 12 years old were the most susceptible to fungal infection.